Written Malay Language Communication Strategies among French Students: (Strategi Komunikasi Penulisan Bahasa Melayu dalam Kalangan Pelajar Perancis) (Jurnal Bahasa, 2015)
This study aimed to determine and categorize the types of written communication strategies in learning Malay among French students. The study, which was based on Dörnyei and Scott's taxonomy of communication strategy, utilized a qualitative and quantitative method of data collection. The subjects consisted of 3rd year Malay degree students at Institut Nationale des Langues et Civilisations Orientales (INALCO) in Paris, France. A total of 10 French students taking the advanced Malay language subject participated in this study. The instruments used in this study were four writing tasks and a strategy checklist. The overall findings based on the writing tasks indicated that among the most frequently used communication strategies were approximation strategy (28.1 percent), the use of all-purpose-word (15.8 percent), circumlocution (12.9 percent) and word coinage (11.7 percent). This study has implications for learners and instructors of Malay to address the strategies used in learning Malay as a foreign language. The results of this study show that language instructors have to consider effective teaching of communication strategies to maximize the effectiveness of Malay language-learning.Keywords: Malay language learning, French students, communication strategies, writing activities, quantitative and qualitative